Molecular medicine : an introductory text - Trent, R. J. (Elsevier Academic Press, 2005)
Molecular medicine is the application of gene or DNA based knowledge to the modern practice of medicine. This book provides contemporary insights into how the genetic revolution is influencing medical thinking and practice on a broad front including clinical medicine, innovative therapies and forensic medicine. * Extensively revised just after the completion of the Human Genome Project, it provides the latest in molecular medicine developments * The only book in Molecular Medicine that has undergone 3 editions * Current practice as well as future developments identified * Extensive tables, well presented figures - resources for further understanding.